2020
DOI: 10.3390/w12071850
|View full text |Cite
|
Sign up to set email alerts
|

Techno-Economic Analysis of RO Desalination of Produced Water for Beneficial Reuse in California

Abstract: There is approximately 508.7 million cubic meters (3.2 million barrels) of oilfield-produced water generated per year across the oil fields of California. While less than 2% of this produced water receives advanced treatment for beneficial reuse, changing regulations and increasing scarcity of freshwater resources is expected to increase the demand for beneficial reuse. This paper reviews onshore-produced water quality across California, relevant standards and treatment objectives for beneficial reuse, identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…• Soda ash softening: A 12-point uniform sample across its single-dimensional space (soda ash dose). • Recarbonation: We start with an initial set of 50 Hammersley points chosen from across the twodimensional space (soda ash and carbon dioxide dose).…”
Section: Mineral Scalingmentioning
confidence: 99%
See 1 more Smart Citation
“…• Soda ash softening: A 12-point uniform sample across its single-dimensional space (soda ash dose). • Recarbonation: We start with an initial set of 50 Hammersley points chosen from across the twodimensional space (soda ash and carbon dioxide dose).…”
Section: Mineral Scalingmentioning
confidence: 99%
“…Many efforts have been focused on incorporating mineral scaling models in bench-scale modules ranging from simple one-dimensional process-scale models to full computational fluid dynamic models relying on either complex mineral scaling models or simple regressions. Some models have considered scaling limitations on RO systems, but they do not perform full treatment train optimization . Models of mineral scaling have been rarely used for the cost optimization of treatment trains at the full system scale, with some studies estimating pretreatment costs from pilot scale data, estimating costs from operational data, , and estimating basic pretreatment design from single dimensional regression . Critically, to our knowledge, the direct incorporation of mineral scaling predictions with rigorous mathematical cost optimization of chemical dosing and RO design in conceptual, high-recovery treatment trains that surpass conventional limitations has never been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Techno-economic feasibility studies were conducted to treat water from Placerita Canyon Oil Field by RO technology. It was found that more than 95% of TDS was removed and suggested that RO technology is viable after the incorporation of structural modifications [30]. Taniguchi et al developed a seawater reverse osmosis (SWRO) membrane, which exhibited excellent boron and TDS removal performance along with high water production.…”
Section: Reverse Osmosis Technology For Tds Removalmentioning
confidence: 99%
“…Few recent studies show a considerable reduction in the electrical energy used by RO systems (2.8 kWh/m 3 ) due to advancements in membranes, however with a relatively poor recovery ratio. [178,179]. On the other hand, the non-payable thermal energy consumed by ADS was reported 39.8 kWh/m 3 entail with payable electrical energy consumption varies between 0.92 to 1.38 kWh/m 3 which significantly reduces the desalination cost even below 0.3 $/m 3 [30].…”
Section: Market Aspects Challenges and Future Perspectivesmentioning
confidence: 99%